2009
DOI: 10.1152/ajpregu.90314.2008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training inducibility of MnSOD protein expression and activity is retained while reducing prooxidant signaling in the heart of senescent rats

Abstract: While the stress response to heat and exercise is limited in the heart with progressive aging, recent data indicate that acute or short-term exercise upregulates the Mn isoform of superoxide dismutase (MnSOD), which may provide protection against ischemia-reperfusion injury and cell death by reducing oxidative stress. Growing evidence indicates that inducible nitric oxide synthase (iNOS) contributes to age-induced increases in oxidative stress and risk of heart failure. We postulated that oxidative stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 58 publications
(86 reference statements)
5
35
0
Order By: Relevance
“…Moreover, the training was able to attenuate the increase on 4-hydroxynonenal protein adducts with the aging. 29 On arterial level similar results were found by another study, which had played increased SOD activity and no change in CAT activity in female Yucatan miniature pigs that had physical training for 16-19 weeks. It was also seen in this same study an increase in the immunocontent of SOD-1, but no modification in CAT immunocontent.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, the training was able to attenuate the increase on 4-hydroxynonenal protein adducts with the aging. 29 On arterial level similar results were found by another study, which had played increased SOD activity and no change in CAT activity in female Yucatan miniature pigs that had physical training for 16-19 weeks. It was also seen in this same study an increase in the immunocontent of SOD-1, but no modification in CAT immunocontent.…”
Section: Discussionsupporting
confidence: 81%
“…Previous data have demonstrated that the major antioxidant enzyme, MnSOD, is most consistently upregulated by exercise training. In this respect, a 12-week training program resulted in upregulation of MnSOD in hearts from old rats [23]. The ability of exercise training to upregulate protective MnSOD protein may explain, at least in part, the improvement of total antioxidant status (TAS) that we also found in diabetic exercised rats.…”
Section: Discussionmentioning
confidence: 77%
“…Neither iNOS nor COX-2 levels were over-expressed in young hearts from exercised animals that exhibited cardioprotection against global IR [54, 58]. Given the obvious link between advancing age and heart disease incidence, cardiac iNOS levels increase with advancing age, though a few weeks of exercise training effectively reverses this effect [103]. Building on this understanding, we also demonstrated that myocardial iNOS and COX-2 levels were not associated with anti-apoptotic effects in aged hearts exposed to IR [54, 58].…”
Section: Mechanisms Of Ischemia Reperfusion Injurymentioning
confidence: 99%